Acute exacerbation of interstitial fibrosis after pulmonary resection - (:unkn) unknown (ELSEVIER SCIENCE INC, 2006)
Idiopathic pulmonary fibrosis is a chronic diffuse lung disease of unknown cause, and a risk factor for increasing morbidity and mortality after lung resection. Acute exacerbation of idiopathic pulmonary fibrosis after lung surgery for lung cancer is rare. The outcome is unsatisfactory despite therapy. We report two cases of acute exacerbation of idiopathic pulmonary fibrosis after resection for lung cancer.